Anita Garibaldi: de heroína à mulher – a trajetória das imagens ficcionais de Ana Maria de Jesus Ribeiro - Rohde, Marina Luísa (2017)
Based on the studies of fictional narratives that re-read the historical past, the research in question analyzes different modalities of historical novels from the representation of Anita Garibaldi (1821–1849), in perspectives that may vary, from the corroboration of the official discourse to its refutation. Such images of this personality, therefore, extend from the perception that she was only a young woman in love and so as to live a great love she would face any obstacle, to the perception of an idealistic and questioning woman, who would take part in wars for political conviction regardless of his loving involvement with a revolutionary sailor. The corpus that provides us with the basis for the study comes from three different contexts: The United States, Brazil and Argentina. The selection of this material considered criteria such as: the belonging of one of the works to the traditional modality of the genre, whose discourse linked to Anita and Giuseppe Garibaldi (1807–1882) is apologetic; a deconstructive perspective of this character hitherto idealized, in a critical production that presents the protagonist who sees in his partner someone to share ideals and for this reason does not accept to be relegated to live in the shadow of that relationship; and also a modality of historical novel whose ideology is mediative in comparison with these two previous productions, aiming at a configuration of Anita that conjugates the representation of both facets commonly evidenced: the lover and the politics. In this sense, each author, through the specificity of his chosen language and modality, approaches the character of historical extraction by a singular prism - the uncritical, the critical and the mediative. To make this analysis possible, in an interamerican dimension, the works selected are: I Am My Beloved: The Life of Anita Garibaldi (1969), written by the American Lisa Sergio, A Guerrilheira (1979), by the Brazilian João Felício dos Santos and Anita cubierta de arena (2003), by the Argentinian Alicia Dujovne Ortiz. Therefore, we show that the fictional images of Anita Garibaldi also trace a historical and sequential trajectory of the hybrid genre of history and fiction. Hence, the theoretical support of this approach, both to the character and to the different modalities of historical romance, finds support in the studies of Aínsa (1991), Menton (1993), Rodríguez (1996), Esteves (2010), Fleck (2011; 2017), Fernández Prieto (2003), to name but a few.